Recovery of Valuable Aromas from Sardine Cooking Wastewaters by Pervaporation with Fractionated Condensation - Pereira, M. João (2022)
Funding Information: The research leading to these results has received funding from Sistema de Apoio à Investigação Científica e Tecnológica (SAICT), Programa de Actividades Conjuntas (PAC) under Multibiore-finery Project (POCI-01-0145-FEDER-016403) and from European Regional Development Fund (ERDF), through the Incentive System to Research and Technological Development, within the Portugal2020 Competitiveness and Internationalisation Operational Program under the project “MobFood—Mobilizing scientific and technological knowledge in response to the challenges of the agri-food market” (POCI-01-0247-FEDER-024524). Maria João Pereira acknowledges Fundação para a Ciência e Tecnologia for Ph.D. fellowship SFRH/BD/119018/2016. This work was supported by the Associate Laboratory for Green Chemistry—LAQV, which is financed by national funds from FCT/MCTES (UIDB/50006/2020). Publisher Copyright: © 2022 by the authors.